The tissue distribution of the mRNA of ghrelin and subtypes of its receptor, GHS-R, in humans. - Gnanapavan, S; Kola, B; Bustin, SA; Morris, D; McGee, P; Fairclough, P; Bhattacharya, S; Carpenter, R; Grossman, AB; Korbonits, M (2002)
Ghrelin is a novel growth hormone-releasing peptide, originally identified in the rat stomach as the endogenous ligand for the growth hormone secretagogue-receptor (GHS-R1a). Ghrelin is involved in the regulation of GH release, but it has recently been suggested that ghrelin may have other actions, including effects on appetite, carbohydrate metabolism, heart, kidney, pancreas, gonads, and cell proliferation. The distribution of ghrelin, its functional receptor (type 1a) and the unspliced, non-functional GHS-R type 1b mRNA expression was investigated in various human tissues using classical and real-time reverse transcription and polymerase chain reaction. GHS-R1a was predominantly expressed in the pituitary and at much lower levels in the thyroid gland, pancreas, spleen, myocardium and adrenal gland. In contrast, ghrelin was found in the stomach, other parts of the gut and, indeed, in all the tissues studied (adrenal gland, atrium, breast, buccal mucosa, esophagus, Fallopian tube, fat tissue, gall bladder, human lymphocytes, ileum, kidney, left colon, liver, lung, lymph node, muscle, muscle, myocardium, ovary, pancreas, pituitary, placenta, prostate, right colon, skin, spleen, testis, thyroid, and vein). GHS-R1b expression was also widespread in all tissues studied. The significance of the widespread tissue distribution of ghrelin remains to be determined. These data suggest that ghrelin might have widespread physiological effects via different, partly unidentified, subtypes of the GHS-R in endocrine and non-endocrine tissues.